PERLINDUNGAN HUKUM TERHADAP LAKI-LAKI YANG MENJADI KORBAN KEKERASAN SEKSUAL - Widjaya, Komang Putri Natalia; Sugama, I Dewa Gede Dana (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 5 (2023), 2023)
The purpose of this study is to examine how the regulation of criminal acts of sexual violence in positive law in Indonesia and how the forms of legal protection are provided to men who are victims of sexual violence. This study uses a normative legal research method, supported by a statutory approach. The results of the study show that the crime of sexual violence has been accommodated in several legal provisions in Indonesia. However, not all of these provisions provide legal protection for men who are victims of sexual violence. From the perspective of the Draft Criminal Code (RKUHP) and the Sexual Violence Act (UU TPKS) both accommodate sexual violence crimes, but in the RKUHP itself the scope of legal protection is still limited to female victims. The Sexual Violence Act itself accommodates in its entirety the legal protection of victims of criminal acts of sexual violence regardless of whether the victim is a man or a woman. Keywords: Legal Protection, Men, Sexual Violence